THE EFFECT OF WATCHING ENGLISH MOVIES “FROZEN” TOWARDS LISTENING COMPREHENSION OF NARRATIVE TEXT AT X GRADE STUDENTS AT SMAN 1 KUOK - Ela Yuhada; Wida Rianti; Lusi Marleni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aimed to examine the effect of watching the English movie Frozen on students’ listening comprehension of narrative texts at the tenth grade of SMAN 1 Kuok. The study was conducted using a quasi-experimental design involving two groups: the experimental group was taught using Frozen as audiovisual media, while the control group received instruction through conventional text-based methods. Pre-tests and post-tests were used to assess students’ comprehension of main ideas, specific details, and inferences. The results indicated a significant improvement in the experimental group, with the mean score increasing from 60.20 to 80.00, while the control group improved from 54.67 to 72.07. An independent sample t-test revealed a significance value of 0.018 (p < 0.05), indicating a statistically significant difference between the two groups. Therefore, it can be concluded that the use of Frozen as audiovisual media had a positive impact on students’ listening comprehension in narrative texts.